Relevance of persistent perfusion deficits on clinical outcomes after successful endovascular treatment: a prospective serial magnetic resonance study - Adrián Valls Carbó; Alicia Palomar; Carlos Laredo; Mariano Werner; Laura Dorado; Sebastià Remollo; Josep Munuera; Josep Puig; Yolanda Silva; Natalia Pérez de la Ossa; Meritxell Gomis; Alejandro Bustamante; et al. (Frontiers in Neurology, 2025)
BackgroundHalf of the patients who undergo successful recanalization after endovascular treatment (EVT) experience poor clinical outcomes. Impaired microvascular reperfusion (IMR) may explain this lack of improvement, but its frequency and clinical significance remain unclear. The study aims to describe the frequency and associated factors of IMR.Materials and methodsWe conducted a study on a cohort of patients with anterior large artery occlusion, treated with EVT at a single center, who achieved mTICI ≥2C. Perfusion MRI was obtained at arrival, up to 2 h after EVT (post-EVT MRI), and on day 5. IMR was observed only on the post-EVT relative cerebral blood volume (rCBV) maps as voxels within the follow-up ischemic lesion, exhibiting a > 15% asymmetry compared to a mirror homolog, in the absence of internal carotid occlusion, hemorrhagic transformation, or arterial reocclusion. Patients with an IMR volume greater than 5 mL were defined as having significant IMR. IMR was analyzed as a binary variable (presence/absence using the 5 mL cut-off) and by total and relative volume.ResultsIMR was present in 8 out of 33 patients (24.2%), with 4 out of 11 (36.4%) having mTICI 2C, and 4 out of 22 (18.2%) having mTICI 3. After adjustment for relevant variables, absolute and relative IMR volumes were associated with higher National Institutes of Health Stroke Scale (NIHSS) scores at 5 days (adjusted beta =0.50 [0.05, 0.96], p = 0.03) and at 24 h (adjusted beta = 0.11 [0.02, 0.19], p = 0.01). No independent associations were found between IMR and the 90-day modified Rankin Scale (mRS).ConclusionIMR is present in one-quarter of patients and is associated with worse early neurological outcomes.